Influence of TiC, TiN and TiC(N) additions on sintering and mechanical properties of injection moulded titanium based metal matrix composites - (:unkn) unknown (MANEY PUBLISHING, 2015)
Titanium (Ti) matrix composites based on Ti and reinforced with TiN, TiC and TiCN particles, were processed following a powder injection molding route: mixing, preparation of feedstock, moulding, debinding and sintering for full densification. The Ti and ceramic powders were dry mixed and molded using a wax based binder. The critical powder loading for injection molding was 55 vol.-% for all samples. Binder debinding was performed using solvent and thermal methods. Following the debinding stage, the samples were sintered for full densification at 1300 degrees C for 2 h in vacuum. Metallographic studies were conducted to investigate densification and the corresponding microstructural changes. The sintered samples were characterized by measuring tensile strength, elongation and hardness. All powders and fracture surfaces of sintered samples were also examined using scanning electron microscope techniques. The sintered densities of injection molded Ti and composites samples were changed with increasing amount of ceramic additions. The addition of TiN, TiC and TiCN improves the densities, tensile strength and hardness.
Keywords: Powder injection molding; Sintering; Titanium composites; STAINLESS-STEEL; POWDER-METALLURGY